The role of human umbilical cord mesenchymal stem cells-derived exosomal microRNA-431-5p in survival and prognosis of colorectal cancer patients. (23rd April 2022) - Qu, Muwen; Li, Junyi; Hong, Zifu; Jia, Fei; He, Yinghua; Yuan, Lingling
Abstract: We aim to discuss the role of miR-431-5p in colorectal cancer (CRC) progression via regulating peroxiredoxin 1 (PRDX1). miR-431-5p and PRDX1 expression were detected in CRC tissues and cells, and the relationship between miR-431-5p expression and prognosis of CRC patients was analyzed. Exosomes were extracted from human umbilical cord mesenchymal stem cells (hUCMSCs) and co-cultured with LoVo cells. MTT assay, flow cytometry and Transwell assay were implemented to test cell viability, apoptosis and invasion and migration ability, respectively. The tumor growth was determined as well, and the binding relation between miR-431-5p and PRDX1 was confirmed. miR-431-5p was downregulated and PRDX1 was upregulated in CRC, and miR-431-5p downregulation was associated with poor prognosis. hUCMSC-Exos suppressed the malignant behaviors of LoVo cells, and overexpression of miR-431-5p further aggravated the inhibitory effect of hUCMSC-Exos on LoVo cells. hUCMSC-Exos inhibited PRDX1 expression via miR-431-5p. PRDX1 was targeted by miR-431-5p. miR-431-5p serves as a prognostic biomarker in CRC, and hUCMSC-Exos transfer of miR-431-5p decelerates CRC cell growth by inhibiting PRDX1.